Concentração, polarização e efeito espaço-temporal da bioeletricidade florestal no Brasil (2000 – 2019) - Santos Júnior, Edvaldo Pereira (2020)
The generation of electricity through forest resources is related to the dynamics of the forest-based sector. This dissertation analyzed the concentration, polarization and spatio-temporal effect of forest bioelectricity in Brazil, from 2000 to 2019. The data for the granting of forest biomass thermoelectric plants were obtained from the National Electric Energy Agency (ANEEL). A bibliometric study and systematic literature review of the spatial analysis of forest bioelectricity was carried out. For regional economics, indicators of concentration, polarization and space economics, exploratory analysis of spatial data and scan statistics were used. The main results showed that in bibliometrics and systematic literature review, there were few studies on spatial analysis of forest bioelectricity, in the web of Science and Scopus databases. In Brazil, the supply of electricity from forest biomass increased from 562.90 MW and 11 thermoelectric plants in 2000 to 3,532.61 MW and 115 thermoelectric plants in 2019, with an average annual rate of 13.20% p.a. for the number of thermoelectric plants and 10.15% p.a. for power granted. The main producing states were: Paraná, Bahia, Espírito Santo and Mato Grosso do Sul. For the state concentration, the CR(4) and the CR(8) showed medium to moderately high concentration and the HHI inferred an atomized distribution. There was an increase in state and plant polarization, provided by the granting of thermal plants to black liquor, starting in 2013. In exploratory analysis of spatial data, the local index (IMoran_Local) evidenced the existence of some high-powered clusters, standing out the Bahia, Espírito Santo and Minas Gerais axis, and the Paraná and Mato Grosso do Sul thermals. The temporal space effect, observed by the scan statistic, showed that the Brazilian forest bioelectricity conglomerates are in the Center-South portion of Brazil associated with the thermoelectric plants with black liquor and forest residues. It can be concluded that the development of this dissertation contributed to a better spatial understanding of Brazilian forest bioelectricity.